Entre maquiagens e costuras: as dramatizações do fazer-ser drag - Ribeiro, Vinícius dos Santos (2025)
Drag queens represent a form of artistic and political expression in which individuals dress and behave in a manner considered exaggerated and extravagant, allowing them to explore various aspects of gender identities by combining elements that are socially considered feminine, such as clothing, gestures, and makeup. In this sense, we can understand drag queens as a dramatization of gender identities (Butler, 2003), that is, as an artistic expression that explores the possibilities and limits of gender in society, bringing them into discussion. Based on this reflection, the main objective of this dissertation is to examine the construction of drag queen styles and identities in the television program RuPaul's Drag Race, an American reality show hosted by RuPaul and created by World of Wonder. Thus, we will analyze four participants in ten episodes of the reality show, taking into account their syncretism of languages, in search of understanding different ways of doing and being drag. Our intention is to contribute to the understanding of drag identities and also to reflections on gender identities, something little explored within discursive semiotics. Thus, based on discursive semiotics (Greimas; Courtés, 2008) and its current developments, we examine the episodes in order to describe the drag styles that are constructed in the program, especially based on the notions of aspectualization, as presented by Fiorin (1989, 2004), and also the notion of style proposed by Discini (2003; 2015). The research dialogues with gender studies, since, based on a perspective in which gender is taken as a performative production, drag queen identities are understood as a kind of staging of gender identities that are projected from their linguistic and discursive production, since drag does not correspond to a gender identity, but to its dramatization, as Butler (2003). In our analyses, we address the constitution of the identity of four participants in the program (Aquaria, Asia O'Hara, Yvie Oddly, and Dawn), created from their speech, clothing, and gestures, but also from the editing of the program and the speech of other drag queens, presenters, and judges. Our investigation led us to identify four distinct styles—bold, traditional, conceptual, and playful—projected by different ways of being and doing drag.